Swimming Injury Risk: an Exploration in Focus - Kadek Yogi Parta Lesmana; I Wayan Wiarta; I Wayan Muliarta (Jurnal Ilmiah Sekolah Dasar, 2025)
This study aims to explore the effectiveness of Swim in Focus digital media based on Yoga-Based Learning as a warm-up tool to reduce the risk of injury in swimming athletes. An exploratory qualitative approach was used involving swimming coaches and athletes as the main informants. Data were collected through semi-structured interviews, direct observation, and documentation of warm-up exercises using the media. The results showed that Swim in Focus was able to improve athletes' physical and mental readiness through a structured, interactive, and easy-to-understand warm-up guide. This media also helps reduce minor injury complaints such as muscle cramps and joint pain by increasing flexibility and body awareness. Coaches reported ease in directing warm-up exercises that were more systematic and engaging for athletes. However, challenges such as limited access to technology and initial understanding of yoga principles need to be overcome to optimize the implementation of this media. The findings confirm that the integration of digital technology and body awareness approach can be an effective strategy in swimming coaching for injury prevention. This research makes an important contribution to the development of innovative and holistic sports learning media.